Marjorie Prime [videorecording (DVD)] - Almereyda, Michael; Hamm, Jon, 1971-; Davis, Geena; Smith, Lois, 1930-; Robbins, Tim, 1958-; Harrison, Jordan (FilmRise, 2017)
In the near future where artificial intelligence has brought about holographic reconstructions of loved ones, 86-year old Marjorie gains a holographic companion in the form of her late husband, but will she take advantage of this opportunity to recreate their life as she wished to have lived it?